Cinema and Society in the British Empire, 1895-1940 - Burns, James. author. aut Link
VII, 243 p.
Keywords: By 1940 going to the movies was the most popular form of public leisure in Britain's empire. This book explores the social and cultural impact of the movies in colonial societies in the early cinema age.